Risk of Seizure-Related Automobile Accidents - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A retrospective case-control study to identify clinical risk factors for seizure-related motor vehicle crashes in 50 patients with epilepsy and 50 matched control patients was performed at Johns Hopkins University, Baltimore, MD.